2008
DOI: 10.1007/s11465-008-0076-4
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric diffuser/nozzle micropump with double pump chambers

Abstract: To eliminate check valve fatigue and valve clogging, diffuser/nozzle elements are used for flow rectification in a valveless diffuser/nozzle micropump instead of valves. However, the application of this type of micropump is restricted because of its pulsating or periodic flow and low pump flux. In this paper, a diffuser/nozzle Si/ Glass micropump with two pump chambers by IC and MEMS technology is designed. The fabrication process requires only one mask and one etch step, so that the fabrication has the advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…He et al developed a piezoelectric pump with three chambers connected in series for a loop cooling system, and the pump had a flow rate most up to 690.6 ml min −1 at an input sinusoidal voltage of 220 V pp and a drive frequency of 110 Hz [25]. Wang et al proposed a piezoelectric micropump with double pump chambers, which obtained the maximum backpressure of 7.8 kPa and the maximum flow rate of 1.5 ml min −1 under in-phase drive mode when driven by a 125 V pp square-wave voltage with 250 Hz excitation frequency [26]. Hu et al proposed a cascade type series-parallel hybrid three-chamber piezoelectric pump, and the experimental results showed that the optimal flow rate and backpressure in asynchronous driving mode exceeded those in synchronous driving mode by 356.54% and 123.53% respectively [27].…”
Section: Introductionmentioning
confidence: 99%
“…He et al developed a piezoelectric pump with three chambers connected in series for a loop cooling system, and the pump had a flow rate most up to 690.6 ml min −1 at an input sinusoidal voltage of 220 V pp and a drive frequency of 110 Hz [25]. Wang et al proposed a piezoelectric micropump with double pump chambers, which obtained the maximum backpressure of 7.8 kPa and the maximum flow rate of 1.5 ml min −1 under in-phase drive mode when driven by a 125 V pp square-wave voltage with 250 Hz excitation frequency [26]. Hu et al proposed a cascade type series-parallel hybrid three-chamber piezoelectric pump, and the experimental results showed that the optimal flow rate and backpressure in asynchronous driving mode exceeded those in synchronous driving mode by 356.54% and 123.53% respectively [27].…”
Section: Introductionmentioning
confidence: 99%